Association between Marital Status and Prognosis in Patients with Prostate Cancer: A Meta-Analysis of Observational Studies - Guo, Zhenlang; Gu, Chiming; Li, Siyi; Gan, Shu; Li, Yuan; Xiang, Songtao; Gong, Leiliang; wang, shusheng (Urology Journal, 2020)
Purpose: The impact of marital status on the prognosis amongst patients diagnosed with prostate cancer remains controversial. Thus, a meta-analysis was performed to determine whether marital status can influence the prognosis in patients with prostate cancer. Materials and Methods: Literature search of the MEDLINE, PsycINFO, Embase and Cochrane Library databases was conducted to identify eligible studies published before April 2020. Multivariate adjusted risk estimates and corresponding 95% confidence intervals (CIs) were extracted and calculated using the random effects model. Results: A total of 11 observational studies comprising 1,457,799 patients diagnosed with prostate cancer were identified. Results indicated that unmarried status (separated, divorced, widowed or never married) was associated with an increased risk of all-cause mortality (hazard ratio, HR = 1.39, 95% CI: 1.30–1.50; P < .001; I2 = 92.2%) compared with married status, especially for divorced and never-married patients. Similarly, being unmarried had an elevated risk of cancer-specific mortality (HR = 1.29, 95% CI: 1.17–1.41; P < .001; I2 = 82.5%) in patients with prostate cancer. A significant difference was also observed between unmarried status and shorter overall survival (HR = 1.37, 95% CI: 1.20–1.56; P < .001; I2 = 94.5%). Conclusion: Results demonstrated that unmarried status is associated with a worse prognosis regarding mortality and survival in patients diagnosed with prostate cancer, particularly in divorced and never-married patients. Hence, further research should explore the potential mechanisms which can benefit the development of novel, more personalised management methods for unmarried patients with prostate cancer.